An Ex-Vivo Study on the Stereoselective Accumulation of Mefloquine Enantiomers in Human Blood Fractions: Accumulation of mefloquine in blood - Souri, Effat; Farsam, Hassan; Akbarpo, Hamid Reza (Iranian Journal of Pharmaceutical Sciences, 2005)
Mefloquine (MFQ), as a racemic mixture is used for the prophylaxis and treatment of malaria. Stereoselective pharmacodynamic and pharmacokinetic differences have been observed for MFQ. In the present study, the human blood was spiked with racemic MFQ. The concentration of MFQ enantiomers in various blood fractions including packed erythrocyte layer, platelet rich plasma and platelet poor plasma was determined. The results showed that the ratio of (+)-MFQ was about 1.5 time higher than (-)-MFQ in packed erythrocyte layer. Results obtained from the separated erythrocytes spiked with racemic MFQ showed no significant difference between the enantiomer concentrations. It can be concluded that the stereoselective accumulation of MFQ enantiomers in erythrocytes might be in relation to protein binding or the presence of other blood cells.